2018
DOI: 10.1016/j.jaci.2018.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Nemolizumab in patients with moderate-to-severe atopic dermatitis: Randomized, phase II, long-term extension study

Abstract: Nemolizumab for up to 64 weeks was efficacious and overall well tolerated in patients with moderate-to-severe atopic dermatitis inadequately controlled by topical therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
137
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(154 citation statements)
references
References 28 publications
6
137
0
8
Order By: Relevance
“…3 Proinflammatory cytokines from T cells and keratinocytes play a key role in the pathogenesis of AD and atopic itch, as previously reviewed. [5][6][7][8][9][10][11] However, there is growing appreciation for the contribution of the nervous system in AD-associated itch. [5][6][7][8][9][10][11] However, there is growing appreciation for the contribution of the nervous system in AD-associated itch.…”
Section: Introductionmentioning
confidence: 99%
“…3 Proinflammatory cytokines from T cells and keratinocytes play a key role in the pathogenesis of AD and atopic itch, as previously reviewed. [5][6][7][8][9][10][11] However, there is growing appreciation for the contribution of the nervous system in AD-associated itch. [5][6][7][8][9][10][11] However, there is growing appreciation for the contribution of the nervous system in AD-associated itch.…”
Section: Introductionmentioning
confidence: 99%
“…Participant flow through study Part A and Part B has been previously reported . Of the 264 patients in the ITT population, 138 who received placebo or nemolizumab in Part A had available WPAI‐AD data and were included in the current analysis (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Details of the study design have been reported previously . Briefly, Part A was an evaluation of four nemolizumab dose regimens (0.1, 0.5 or 2.0 mg/kg s.c. every 4 weeks [Q4W] or 2.0 mg/kg s.c. every 8 weeks [Q8W]).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…that is a central mediator of itch markedly reduced pruritus in two phase II studies, but had only moderate effects at EASI scores. 122,123 Targeting epithelial cytokines such as IL-17C and fezakinumab (IL-22 antibody) or IL-22R are at early stages of development. There is clear evidence that AE is a heterogeneous disease, probably comprising several endotypes.…”
Section: Future Developments: Focussing On Type 2 Immunity and Epitmentioning
confidence: 99%